Where Is the Core of the Volcano? The Undetermined Origin of Primary Restless Legs Syndrome - İŞAK, BARIŞ; ULUÇ, KAYIHAN; AĞAN YILDIRIM, KADRİYE; TANRIDAĞ, TÜLİN (TAYLOR & FRANCIS LTD, 2011)
An association between small fiber neuropathy and primary Restless Legs Syndrome (RLS) is suggested since both of them share common characteristics. Our aim was to investigate the existence of autonomic neuropathy on the basis of autonomic tests. The patients and the age-matched controls were evaluated with Neuropathy Symptom Profile and Autonomic Symptom Profile, nerve conduction studies (NCS), and autonomic tests. Patients suffered from neuropathic and autonomic complaints obviously. There was no significant difference for NCS, heart rate variability tests, and sympathetic skin responses (SSRs) among patients and controls. Since both the NCSs and the autonomic tests were within normal, the complaints were considered to be the consequences of the problem in sensory integration due to the dysfunction of the caudal diencephalic All group, rather than a neuropathic process. The cardiac autonomic imbalance possibly emerges as a consequence of arousal periods prior to or during the Periodic Leg Movements (PLM) episodes during sleep, but not due to autonomic neuropathy.
Keywords: Heart rate variability; peripheral neuropathy; Restless Legs Syndrome; sympathetic skin response; SURAL NERVE-CONDUCTION; RAT SPINAL-CORD; CUTANEOUS SILENT PERIOD; FICTIVE LOCOMOTION; PRESYNAPTIC INHIBITION; CLINICAL UTILITY; SYMPTOM PROFILE; SENSORY NEURONS; FIBER DENSITY; GROUP-IA